2014
DOI: 10.4274/tjod.05617
|View full text |Cite
|
Sign up to set email alerts
|

The effect of first chromosome long arm duplication on survival of endometrial carcinoma

Abstract: Objective:The aim of this study is to investigate the effect of first chromosome long arm duplication (dup(1q)) in cases with endometrial carcinoma detected with array based comperative genomic hybridization (aCGH) on survival from the cancer.Materials and Methods:A total of 53 patients with the diagnosis of endometrial carcinom due to endometrial biopsy and who have been operated for this reason have been allocated in the study. Frozen section biopsy and staging surgery have been performed for all the cases. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
(32 reference statements)
0
1
0
Order By: Relevance
“…3A). Sever et al (45) also reported that gains in 1q had a negative impact on survival in EC patients. In addition, aberrations in 1q have also been described in Müllerian tumors of mesonephric type, though neither of our cases showed histologic features of this tumor type, despite the fact that case 4 also harbored KRAS mutation, a finding also documented in a high percentage of mesonephric carcinomas (46)(47)(48).…”
Section: Discussionmentioning
confidence: 97%
“…3A). Sever et al (45) also reported that gains in 1q had a negative impact on survival in EC patients. In addition, aberrations in 1q have also been described in Müllerian tumors of mesonephric type, though neither of our cases showed histologic features of this tumor type, despite the fact that case 4 also harbored KRAS mutation, a finding also documented in a high percentage of mesonephric carcinomas (46)(47)(48).…”
Section: Discussionmentioning
confidence: 97%